Senescence in hepatic stellate cells as a mechanism of liver fibrosis reversal: a putative synergy between retinoic acid and PPAR-gamma signalings - Panebianco, Concetta; Oben, Jude A; Vinciguerra, Manlio; Pazienza, Valerio (Clinical and experimental medicine, 2017)
Hepatic stellate cells (HSCs), also known as perisinusoidal cells, are pericytes found in the perisinusoidal space of the liver. HSCs are the major cell type involved in liver fibrosis, which is the formation of scar tissue in response to liver damage. When the liver is damaged, stellate cells can shift into an activated state, characterized by proliferation, contractility and chemotaxis. The activated HSCs secrete collagen scar tissue, which can lead to cirrhosis. Recent studies have shown that in vivo activation of HSCs by fibrogenic agents can eventually lead to senescence of these cells, which would contribute to reversal of fibrosis although it may also favor the insurgence of liver cancer. HSCs in their non-active form store huge amounts of retinoic acid derivatives in lipid droplets, which are progressively depleted upon cell activation in injured liver. Retinoic acid is a metabolite of vitamin A (retinol) that mediates the functions of vitamin A, generally required for growth and development. The precise function of retinoic acid and its alterations in HSCs has yet to be elucidated, and nonetheless in various cell types retinoic acid and its receptors (RAR and RXR) are known to act synergistically with peroxisome proliferator-activated receptor gamma (PPAR-gamma) signaling through the activity of transcriptional heterodimers. Here, we review the recent advancements in the understanding of how retinoic acid signaling modulates the fibrogenic potential of HSCs and proposes a synergistic combined action with PPAR-gamma in the reversal of liver fibrosis.
Keywords: Signal Transduction; Liver Cirrhosis; jaterní hvězdicovité buňky; Humans; Antineoplastic Agents; PPAR gamma; keratolytika; jaterní cirhóza; protinádorové látky; signální transdukce; tretinoin; Hepatic stellate cells; Tretinoin; Retinoic acid; Keratolytic Agents; Hepatic Stellate Cells; lidé; Fibrogenesis; PPAR gama